The Prospective Elementary School Teacher Students' Opinion in Online Learning Using Virtual Learning Environments - Rachmadtullah, Reza; Tanod, Mareyke Jessy; Irawan, Nico; Mascarinas, Ada Marie; Anshoriyah, Sofiyatul (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
Digital-based education, including virtual learning environments, has gained traction within the community. However, it is essential to acknowledge that not all online learning experiences are without drawbacks; they come with advantages and disadvantages. Therefore, the primary objective of this study is to investigate the perspectives of student candidates aspiring to become elementary school teachers regarding their experiences with online learning via virtual environments. The research methodology employed here is descriptive and qualitative. The study encompasses a participant pool of 60 students in their fifth semester. The findings of this research reveal that, on the whole, students exhibit satisfaction and comfort in using virtual learning environments. The incorporation of virtual learning environments contributes to a resource-efficient learning approach. Additionally, implementing these virtual environments nurtures self-confidence and independence among learners. Notably, the most significant advantage of online learning via virtual platforms from home is the ability to store learning materials, enabling students to revisit them as needed. This condition is made feasible by downloading online learning materials, allowing children to save and access them conveniently. However, challenges persist, including weak internet signals, limitations in delivering all materials online, and the students' demand for practical material examples.